2017
DOI: 10.1259/bjr.20170633
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of volume calculation and margin growth accuracy on treatment planning systems for stereotactic radiosurgery

Abstract: Differences between volume calculation methods may lead to 5-10% variation in reported volumes from different TPS. This should be taken into account when comparing multicentre studies, and it is recommended that a minimum volume of 0.05 cm be used for any near-point doses to allow more consistent comparisons. When margins are added to small structures, there may be up to 40% difference to nominal margin size. Such differences are still small compared to interobserver variation in delineation. Advances in knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…D 0.5cc ) are now reported to 0.1 cc to become more in line with international practice. The volume of 0.1 cc was also chosen as this is considered a large enough volume to be reproducible between treatment planning systems (TPSs) [26], acknowledging that ICRU report 91 [27] and the AAPM TG-101 report [18] recommend that maximum dose constraints be applied to 0.035 cc. It is considered that, at present, there is insufficient high-quality prospective evidence to justify the ongoing use of D 0.5cc as before.…”
Section: General Principlesmentioning
confidence: 99%
“…D 0.5cc ) are now reported to 0.1 cc to become more in line with international practice. The volume of 0.1 cc was also chosen as this is considered a large enough volume to be reproducible between treatment planning systems (TPSs) [26], acknowledging that ICRU report 91 [27] and the AAPM TG-101 report [18] recommend that maximum dose constraints be applied to 0.035 cc. It is considered that, at present, there is insufficient high-quality prospective evidence to justify the ongoing use of D 0.5cc as before.…”
Section: General Principlesmentioning
confidence: 99%
“…The CT image, true volume, and transferred observer volumes were then exported and analyzed in MIM. There could be potential differences in volume calculation and rendering between different systems ( 27 , 28 ). To confirm fidelity of volumes following transfer from Eclipse to MIM, volumes reported by the two systems were compared, and the difference was negligible 0.01 ± 0.01 cc.…”
Section: Discussionmentioning
confidence: 99%
“…Large inter-observer variation was particularly manifest with the smallest brain metastases. Over-and under-contouring may be due to fusion accuracy, variation between TPS volume calculation methods [22] or differences in clinician training, ethos and accuracy. However, we also observed that interpretation of images and uncertainty over the precise target led to discrepancy, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There was potential variation between volume calculation and display between different systems, which could amount to 5e10% differences [22,23]. Some centres opted to delineate on the MRI scan and then interpolate the volume on to the computed tomography scan, which was then used for export and analysis.…”
Section: Limitationsmentioning
confidence: 99%